The Diversity of Molluscs in Seagrass Ecosystem of Wondama Bay, West Papua, Indonesia - Aji, Ludi Parwadani; Widyastuti, Andriani; Hadiyanto, Hadiyanto (Marine Science Department Diponegoro University, 2025)
Papua, Indonesia is located in the Coral Triangle and is home to many marine creatures. Some areas of Papua, however, remain underexplored, particularly in terms of the diversity of mollusc and their seagrass bed habitat. This research aims to document benthic mollusc and seagrass species in Wondama Bay Regency and assess how habitat, temperature, and geographic location affect mollusc diversity and composition. Field data collection was conducted at nine sampling stations. A total of 197 benthic mollusc species was recorded, consisting of 53 species from 19 families of bivalves and 144 species from 40 families of gastropods. This suggests that mollusc species in Wondama Bay Regency still need further exploration which could reveal additional species. The bivalve Tellina sp. and gastropod Mitrella scripta were found in all nine sampling areas. Furthermore, nine species of seagrasses were recorded, with Enhalus acoroides and Cymodocea rotundata found at all sites. The number of seagrass species in our study is considerably high. The seagrass species richness ranged from three to eight species, while the percent cover varied from 13 % to 65 % across sites. This research found that temperature, seagrass species, and geographic location did not significantly impact the mollusc species composition among sites. Whereas, seagrass coverage showed as an important driver of mollusc community assemblages, highlighting the importance of seagrass bed protection for mollusk diversity. This finding may assist stakeholders in advancing marine conservation efforts and encouraging the sustainable utilization of marine resources particularly in Wondama Bay Regency, Papua.